Pengalaman dan Gangguan Aktivitas Seksualitas Klien Penyakit Jantung Koroner - Muhammad Amin; Larra Fredrika; Delvi Duwi Kartika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine how the experience of sexual activity disorders in clients with coronary heart disease in Dr. M. Yunus Bengkulu. This type of research used in this research is qualitative, with the phenomenological method. This study resulted in four (4) themes, namely: aspects of knowledge about coronary heart disease, aspects of treatment, aspects of sexual activity disorders in clients with coronary heart disease, emotional aspects. The results showed that sexual activity disorders in coronary heart patients were lack of appetite, stimulation, orgasm, and dyspareunia. In conclusion, the client's efforts to reduce pain and improve when having a husband and wife is by using lubricants. Keywords: Coronary Heart, Experience, Sexuality